THE POLITICS OF LEGITIMACY: ANALYSING SOCIAL ASSISTANCE PROGRAMS IN YOGYAKARTA CITY 2020-2025 - Salafian, Jen (Kemudi, 2025)
Political legitimacy practised by the Yogyakarta City Regional People's Representative Council (DPRD) is doubly present with the influence of Javanese culture that takes legitimacy for granted. This research aims to find out why the dominance of the Yogyakarta City Government is accepted as legitimate by the Yogyakarta City DPRD towards the community of social assistance recipients in 2020-2025 and describe the political oversight model. The method used is descriptive qualitative with shadowing techniques reinforced by interviews, which will try to find facts and realities in the field. The results showed that a new model was formed, namely double oversight, which constructs power according to Javanese culture carried out by the DPRD from the criteria of police patrol and fire alarm oversight. This is supported by the recognition of the community, which is quite solid against the background of the community's alarming situation. This can be seen from the lack of involvement of DPRD in determining policies to accelerate the realisation of social assistance programs, and the power in making policies is dominated by the executive agency, in this case, the Mayor of Yogyakarta, which is influenced by Javanese power motives.